Neuroplasticity associated with anterior cruciate ligament reconstruction - Grooms, D. R.; Page, S. J.; Nichols-Larsen, D. S.; Chaudhari, A. M. W.; White, S. E.; Onate, J. A. (Journal of Orthopaedic & Sports Physical Therapy, 2016)
Study Design: Controlled laboratory study. Background: Anterior cruciate ligament (ACL) injury may result in neuroplastic changes due to lost mechanoreceptors of the ACL and compensations in neuromuscular control. These alterations are not completely understood. Assessing brain function after ACL injury and reconstruction with functional magnetic resonance imaging (fMRI), provides a means to address this gap in knowledge. Objective: To investigate brain activation differences during knee flexion/extension in persons who have undergone ACL reconstruction (ACLR) and matched controls. Methods: Fifteen participants who had undergone left ACLR (38.13±27.16 months post-surgery) and 15 healthy controls matched on age, height, mass, extremity dominance, education level, sport participation, and physical activity level participated. fMRI data were obtained during a unilateral knee motor task consisting of repeated cycles of knee flexion and extension. Results: Participants with ACLR had increased activation in the contralateral motor cortex, lingual gyrus, and ipsilateral secondary somatosensory area and diminished activation in the ipsilateral motor cortex and cerebellum when compared to healthy matched controls. Conclusion: Brain activation for knee flexion-extension motion may be altered following ACLR. The ACLR brain activation profile may indicate a shift towards a visual-motor strategy as opposed to sensory-motor strategy to engage in knee movement